Navigating in the gray area of coach-athlete relationships in sports: Toward an in-depth analysis of the dynamics of athlete maltreatment experiences - Marsollier, E.; Hauw, D. (Frontiers in Psychology, 2022)
Several studies have revealed the abusive behaviors directed against athletes in various sports contexts, but knowledge about the processes by which the athletes realize and accept or reject maltreatment is underdeveloped. Thus, it is difficult to establish a solid scientific basis for characterizing the mechanisms of maltreatment from the athletes' perspective regarding the forms of maltreatment they endure and the impact on their performance and wellbeing. The main goals of this paper are to show how the enactive approach (including theoretical assumptions and methodological standards) can meet these challenges, as it is well-suited to (a) describe the evolving interactions between athletes and the sports situations that lead to maltreatment (i.e., navigating in the gray area of coach-athlete relationships), (b) identify those alert landmarks that help us assess the level of risk of athlete maltreatment, and (c) provide concrete guidelines to prevent and deal with sports-related maltreatment. We illustrate our approach by a case study that examines the experience of a retired high-level boxer who faced several forms of maltreatment. Our results reveal a dynamic change in the interactions between the boxer and the maltreatment situations that led her through (a) Acceptance (i.e., future-oriented positive involvement), (b) Regulation attempt (i.e., negative feelings about weight loss, exhaustion and loneliness, questioning the compromise between performance and health, acceptance and loneliness), (c) Distancing (i.e., reopening to others) and (d) Rejection (i.e., rebellion and the decision to stand up to her coach and leave). Based on our results, we present concrete guidelines to prevent and address sports-related maltreatment, with four progressive alert landmarks that help situate the athlete in the gray area of coach-athlete relationships and suggest a "timeline" of maltreatment escalation with key warnings.